Effect of unfractionated heparin and low molecular weight heparin on the clotting of platelet-reduced whole blood: an in-vitro study utilizing thromboelastography. Issue 5 (July 2021) - Chung, Jason; Stevic, Ivan; Gantioqui, Jorell; Atkinson, Helen; Chan, Anthony K.C.; Chan, Howard H.W.
Abstract : N/A: Treatment of venous thromboembolism with concomitant thrombocytopenia is challenging. The platelet threshold for safe administration of anticoagulants is under debate, with minimum platelet count of 50 × 10 9 /l being recommended as the safe cutoff. However, some evidence suggests administration of anticoagulants may still be safe at platelet levels of 30 × 10 9 /l. Therefore, we developed an in-vitro thromboelastography (TEG) study to examine the effect of therapeutic or prophylactic levels of unfractionated heparin (UFH) and low molecular weight heparin (LMWH) on the clotting profile of platelet-reduced whole blood. Using magnetic bead-based antibody chromatography, platelets were removed to achieve platelet-depleted blood (<10 × 10 9 /l of platelets). Platelet-depleted blood was then mixed with whole blood to produce blood samples with platelet counts of 30 × 10 9, 50 × 10 9 and 150 × 10 9 /l. These blood samples were incubated with therapeutic or prophylactic levels of UFH or LMWH in disposable TEG cups. Clotting was initiated with 10 mmol/l calcium and optimized tissue factor levels for each anticoagulant used (2.25 pmol/l for UFH and 2.05 pmol/l for LMWH). Clotting was monitored by TEG at 37 °C for 180 min. The following TEG parameters were evaluated: R (time to clot), maximum amplitude (strength of clot) and area under the curve in 15 min (overall speed and strength of the clot at 15 min of clotting). No statistically significant differences were observed between platelet counts of 30 × 10 9 and 50 × 10 9 /l for R, maximum amplitude or area under the curve in 15 min for most of the therapeutic and prophylactic doses of UFH and LMWH tested in this study. Use of anticoagulants compromised all of the TEG parameters relative to a normal platelet count of 150 × 10 9 /l, in a dose dependent manner. The current study demonstrates that in-vitro clotting is impaired with use and increasing doses of anticoagulants. Despite this observation, we did not observe a significant difference in clotting between platelet levels of 30 × 10 9 and 50 × 10 9 /l. Overall, this work provides further insight in the debated use of anticoagulants in patients with venous thromboembolism and concomitant thrombocytopenia, and provides support for possible use of anticoagulants at lower platelet thresholds.